Gender disparities in valuing remote and hybrid work in Latin America - Ana Maria Diaz Escobar; Luz Magdalena Salas; Claudia Piras; Agustina Suaya (Inter-American Development Bank (IDB), 2024)
This study sheds light on the growing trend and gender dynamics of workplace flexibility in Latin America, underscoring the importance of remote work options in the region's labor market. We explore gender differences in willingness to pay (WTP) for remote work arrangements in Latin America, using a discrete choice experiment across five countries: Colombia, Peru, Mexico, Chile, and Argentina. Results reveals a general trend among Latin American workers to trade off some wage in exchange for more remote work options, both fully and partially remote, in two male-dominated occupations: Manufacturing and information technology. On average, participants agreed to sacrifice around 10% of their wage for hybrid jobs (80% remote, 20% on-site). The WTP for fully remote work was slightly lower, at about 6% of the wage. Women exhibit a higher WTP for flexibility compared to men, with a 62.5% higher willingness across estimates for hybrid arrangements. Moreover, women's inclination towards fully remote options was distinct, as they showed a positive WTP (up to 10% of their salary) for such arrangements, whereas men exhibited no willingness to reduce their wages for fully remote roles.
Keywords: J22; J31; J41; J51; J71; 330; Willingness to Pay; Flexible Work Arrangements; Discrete Choice Experiment